New lease accounting standard for lessee: are academia ready? / Zuraini Yaacob - Yaacob, Zuraini (Faculty of Accountancy, UiTM Kedah, 2019)
The purpose of this article is to summarise the accounting for lease in lessee's books under new standard for lease. A lease refers to an agreement where by the legal owner of an asset (lessor) conveys to the user of the asset (lessee) the right to use an asset for a period of time in exchange for consideration. MFRS16 Leases was issued by Malaysian Accounting Standards Board (MASB) in April 2016 to prescribe the principles for the recognition, measurement, presentation and disclosure of leases.